Meningkatkan Hasil Belajar Matematika Materi Bangun Ruang Menggunakan Alat Peraga Kubus dan Balok pada Siswa Kelas VI UPTD SDN 3 Bakam - Rozali Rozali; M Iqbal Arrosyad; Gatot Afrianto (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2024)
study aims to improve students' learning outcomes in understanding geometric shapes, particularly in surface area and volume, through the use of cube and rectangular prism teaching aids. Sixth-grade students at UPTD SD Negeri 3 Bakam often struggle with this topic, primarily due to difficulties in grasping multiplication concepts and related formulas. The method used in this research is a cooperative learning approach with teaching aids designed to facilitate student comprehension. The study was conducted in two cycles. In the pre-cycle phase, only 33.33% of the 21 students scored above the minimum passing grade (70), while 66.67% scored below it. After applying the method in Cycle I, learning mastery increased to 61.33%, with 12 students achieving a score of 70 or above. In Cycle II, learning outcomes improved significantly, with 95.33% of students achieving mastery. Additionally, the teacher's teaching effectiveness improved, with an average score of 82.38, categorized as good. The results indicate that the use of cube and rectangular prism teaching aids can enhance students' understanding of surface area and volume concepts, contributing significantly to their academic performance improvement